URBAN FUTURE 21: a global agenda for twenty-first century cities by Peter Hall & Ulrich Pfeiffer - Laubscher, Jacques (Acta Structilia, 2002)
With the publication of URBAN FUTURE 21: a global agenda for twenty-first century cities, Hall and Pfeiffer present a document that has depth in quality, and a text that is integrated with graphics, references to policies of international humanitarian bodies, as well as a bibliography including references from Charles Dickens (1854) to a readily accessible Website. Openended questions are posed throughout the book forcing the reader to form an opinion, or at least think about one.